EFFECTS OF CHARCOAL UTILIZATION AS A SOURCE OF DOMESTIC ENERGY IN POTISKUM LOCAL GOVERNMENT AREA OF YOBE STATE - Abdullahi, Tijjani Yahaya; Ismail, Faiz Tijjani; Gero, Aminu M. (FUDMA Journal of Sciences, 2026)
Primary and secondary data were obtained through questionnaire administration, field observation, interview and observations,  as well as data from journals, literature and Newspaper respectively.  A simple random sampling technique was adopted for the purpose of the research where 150 questionnaires were administered in the selected sample ward. Thus, the finding of the study reveals that majority of the population (70%) utilized charcoal for domestic utilization not knowing it environmental health effect. It further reveals that charcoal as source of domestic energy has detrimental impact to the community as it causes health problem such as asthma, bronchioles, skin rashes and itching and eye problem and also environmental problem such as soil degradation, pollution among other. Hence the study  recommended that provision of alternative source of energy such as cooking gases or the use biomass energy which will reduce emission and aid in reducing both health and environmental menace of charcoal as source of domestic energy. Government should provide alternative source of energy utilization which are less harm to the environment and to human health such as solar energy, electrical energy, wind energy among other. Government should also impose policy on the use of alternative energy and conducts public awareness and enlightenment with regard to the effects and consequences of charcoal utilization to reduce air pollution and other health related issues.
Keywords: Charcoal; Energy; Utilization; Source; Effects on health issues